Adjustment to divorce among Iranian and Chilean women: an exploratory study - Asanjarani, Faramarz (Mental health, religion & culture, 2021)
This study aimed to explore the relative contribution of the country of origin associated with adjustment to divorce (AD) and its interactions with several correlate among women from two different cultures, i.e., Iran and Chile. With that purpose, 292 participants, including Muslim Iranian (n=147) and Chilean (n=145) women, completed an AD questionnaire. A hierarchical multiple linear regression test was used to examine the main effect of country of origin, as well as several correlates of AD and their interaction effects. The country of origin was strongly related to AD, with Iranian women reporting lower adjustment levels than Chilean participants. We also identified that the level of prior relationship satisfaction and a new romantic relationship were associated with AD. No interaction effects were identified.